Facile Fabrication of PEGylated Fluorescent Organic Nanoparticles with Aggregation‐Induced Emission Feature via Formation of Dynamic Bonds and Their Biological Imaging Applications. Issue 20 (22nd August 2016) - Long, Zi; Liu, Meiying; Wan, Qing; Mao, Liucheng; Huang, Hongye; Zeng, Guangjian; Wan, Yiqun; Deng, Fengjie; Zhang, Xiaoyong; Wei, Yen
Abstract : Driven by the high demand for sensitive and specific tools for optical imaging, fluorescent nanoprobes with various working mechanisms and advanced functionalities are flourishing at an incredible speed. This work reports the design and fabrication of aggregation‐induced emission (AIE)‐active fluorescent organic nanoparticles (FNPs) via forming dynamic phenyl borate between diol containing hydrophobic AIE dye (APD‐PhCHO) and phenylboronic acid pendant hydrophilic polymers (PEGMA‐VPBA) within 30 min. The final AIE‐active APD‐PhCHO‐PEGMA‐VPBA FNPs display high water dispersibility and strong fluorescence emission because of their amphiphilic properties and AIE feature. Biological evaluation suggests that APD‐PhCHO‐PEGMA‐VPBA FNPs possess negative effect on HeLa cells and desirable optical properties for biological imaging. More importantly, phenyl borate is a dynamic bond with pH and glucose responsiveness. Furthermore, different functions can be designed and introduced into these AIE‐active systems through adoption of different monomers for good applicability of free radical polymerization. Therefore, this work provides a novel platform for preparation of multifunctional AIE‐active nanosystems with responsiveness for various biomedical applications. Abstract : Fluorescent organic nanoparticles with an aggregation‐induced emission feature, good water dispersibility, and good biocompatibility have been fabricated via formation of dynamic phenyl borate bonds between the diol group of ADP‐PhCHO and phenylboronic acid group of PEGMA–VPBA in a facile one‐pot strategy.